Improvement of consumer properties of melted cheese applying vegetable protein - Шевченко, Олена Євгеніївна (Eastern-European Journal of Enterprise Technologies, 2012)
This work is devoted to the development and merchandising evaluation of new combined melted cheese, applying vegetable ingredients, to enhance biological value, improve the nutritional properties and reduce cholesterol levels. The work includes the research of samples of developed melted cheese, their expert evaluation; study of merchandising quality properties of cheese, namely, rheological and organoleptic. The influence of the quantitative substitution of raw milk by the vegetable protein sofu in cheese recipes and its optimal amount were studied and determined. The effectiveness and appropriateness of usage of vegetable protein, produced from soya beans, were proven. It was discovered that the substitution of raw milk by soya protein without the quality deterioration is possible only in a limited amount (up to 10%). With the increase of the sofu (10%), the deterioration of consistency, taste and flavor was observed.